Energy finance, digital financial inclusion, accountability and sustainable development: evidence from BRICS - Liu Xia; Nazneen Fatema (Humanities & Social Sciences Communications)
Abstract Achieving sustainable development in emerging economies requires a strategic balance between financial investments, governance structures, and technological advancements. This study examines the interconnections between Fossil Fuel Energy Finance (FFEF), Renewable Energy Finance (RNEF), Digital Financial Inclusion (DFIN), and Governance Accountability (GAB) in driving Sustainable Development (SD) in BRICS countries over the period 2000–2023. Employing a dynamic Qualitative Comparative Analysis (QCA), we identify three key configurations that foster high SD: (1) a pathway where high FFEF is complemented by strong governance accountability and widespread digital financial inclusion, ensuring both energy security and financial accessibility; (2) a second pathway where high levels of FFEF, coupled with increased investment in renewable energy and an expansive digital financial system, support a transition towards a more balanced and sustainable energy mix; and (3) a third pathway in which high RNEF, effective governance accountability, and digital financial inclusion work in tandem to enhance sustainable growth by promoting clean energy adoption and economic resilience. To validate the robustness of these configurations, we conduct additional empirical tests using Fully Modified Ordinary Least Squares (FMOLS), which confirm the stability of our findings and reinforce the significance of these financial and governance factors in shaping sustainable outcomes. Our study contributes to the existing literature by offering a comprehensive, evidence-based understanding of how different financial and institutional mechanisms interact to drive sustainability in emerging economies. The findings provide valuable insights for policymakers, energy strategists, and financial planners, highlighting the importance of a holistic approach that integrates traditional and renewable energy finance with digital financial tools and governance reforms. By shedding light on the optimal combinations of factors that lead to sustainable development, this research underscores the necessity of cohesive and targeted policies to accelerate the transition toward a more inclusive, accountable, and environmentally sustainable economic future for BRICS nations and beyond.